MENINGKATKAN KETERAMPILAN MEMBACA PUISI SISWA KELAS IV SD NEGERI CALINGCING DENGAN MENGGUNAKAN MEDIA AUDIO VISUAL - Ayu Nurhayati Indah; Rizki Hadiwijaya; Deni Chandra (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research was motivated by students' low poetry reading skills and the use of less interesting learning media. The aim of this research is to improve poetry reading skills using audio-visual media for class IV students at SDN Calingcing. This type of research is Classroom Action Research (PTK) which is carried out in 2 cycles. The research subjects were 30 class IV students at SDN Calingcing, consisting of 16 women and 14 men. This research is divided into three stages, namely pre-action, cycle I and cycle II. Based on the results of research at the pre-action stage, it was found that 5 students (16.66%) had completed their poetry reading skills and 25 students (83.33%) had not completed them. KKM with an average value of 61.16. Furthermore, in cycle I the results of poetry reading skills were 24 students (80%) completed and 6 students (20%) not completed. KKM with an average value of 77.50. Then, 30 students (100%) completed cycle II and were above the KKM with a score of 68. The average score obtained by all students was 80.50. Thus, it can be concluded that the poetry reading skills of class IV students at SDN Calingcing using audio visual media have increased.